rationalization costs RATIONALIZATION OF COSTS UNDER THE USE OF MIRRORS SYSTEMS AS AN ALTERNATIVE TO FOSSIL ENERGY - Asadi, Shaymaa (International Journal For Research In Business, Management And Accounting, 2021)
The importance of research is to rationalize the cost of electricity production through the use of Concentrated Solar Power Systems as alternative clean and renewable energy from the fossil energy as one of the modern methods in electric field which provides the friendly-energy of environment in sufficient quantities and reduces emissions and pollutants that cause global warming. In addition to calculation of costs by using the costs management tools for the purpose of rationalizing costs and thus rationalizing government expenditure. The problem of research is the lack of electricity in Iraq and insufficient quantities which don’t meet the citizen’s needs. As well as frequent and continuous interruptions and poorly equipped importation from out of Iraq leading to huge production costs and increased pollution and lack of interest in cost management tools in Iraqi government institutions, which lead to increase in government spending. The aim of this research is to rationalize electricity production costs by using the Concentrated Solar Power systems as an alternative to conventional energy.in additional to calculation of rationalization costs through the activity base costs system (ABC).The hypothesis of the research on base use the Concentrated Solar Power Systems is environmentally friendly as an alternative to fossil energy and works to reduce (costs, emissions, and pollutants) in additional to Rationalize costs by use activity base costing system (ABC) for calculation of the rationalization. The most prominent results through the concentrated solar power systems we can fulfil the reduction and led to the rationalization of costs and provide the (quality, efficiency, non-pollutions, continuous power, environmentally friendly, sustainability tools, citizen’s satisfaction).